2001
DOI: 10.1021/ic001419t
|View full text |Cite
|
Sign up to set email alerts
|

Trinuclear Zn(II) and Cu(II) Homo and Heterotrimetallic Complexes Involvingd-Glucopyranosyl and Biscarboxylate Bridging Ligands. A Substrate Binding Model of Xylose Isomerases

Abstract: Reactions of MCl(2).nH(2)O with N,N'-bis(D-glucopyranosyl)-1,4,7-triazacyclononane ((D-Glc)(2)-tacn), which was formed from D-glucose and 1,4,7-triazacyclononane (tacn) in situ, afforded a series of mononuclear divalent metal complexes with two beta-D-glucopyranosyl moieties, [M((D-Glc)(2)-tacn)Cl]Cl (M = Zn (11), Cu (12), Ni (13), Co (14)). Complexes 11-14 were characterized by analytical and spectroscopic measurements and X-ray crystallography and were found to have a distorted octahedral M(II) center ligate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…The vicinal functional groups feature several donor atoms capable of forming stable complexes with transition metals [7] and offer several possibilities to introduce additional donor groups into the sugar backbone. Well-known modification strategies are N-glycosylation of polyamines [8,9] and nucleophilic substitution of bromoethyl-O-glycosides. [10] TEMPO oxidation of the secondary hydroxyl group at C6 results in the formation of uronic acids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The vicinal functional groups feature several donor atoms capable of forming stable complexes with transition metals [7] and offer several possibilities to introduce additional donor groups into the sugar backbone. Well-known modification strategies are N-glycosylation of polyamines [8,9] and nucleophilic substitution of bromoethyl-O-glycosides. [10] TEMPO oxidation of the secondary hydroxyl group at C6 results in the formation of uronic acids.…”
mentioning
confidence: 99%
“…[17][18][19][20] In particular, their copper(II) compounds show a considerable tendency to self-aggregate affording oxoidobridged oligonuclear complexes with unexpected magnetic properties induced by hydrogen bonding between the constituting glucose ligands. [17] The formation of oxygen bridged polynuclear compounds is a general feature for transitionmetal complexes with carbohydrate derivatives as ligands, [21,8] which is usually prevented by the presence of appropriate coligands to coordinatively saturate the metal ion. Nevertheless very little is known about relevant carbohydrate-based polynuclear complexes.…”
mentioning
confidence: 99%
“…These findings are in agreement with its embedding in the centre of a distorted octahedron. With respect to the flexibility of Zn(ii) in the formation of different complex geometries the complex fits within Fuchs et al (2014), Barnard et al (2009), Ryu et al (2003, or Tanase et al (2001), even if for the latter case larger structural deviations are observed due to larger structural differences in the ligand constitution.…”
Section: Commentmentioning
confidence: 55%
“…The structures of Zn II complexes with ligands stabilizing comparable complex geometries can be found in Barnard et al (2009), Ryu et al (2003) or Tanase et al (2001). In Tanase et al (2001), the ligands show comparable N,N,O,O-coordination with respect to a different ligand backbone whereas in Ryu et al (2003) and Barnard et al (2009), the ligands with N,N,N,N-coordination are diaminobenzene derivatives.…”
Section: Related Literaturementioning
confidence: 95%
See 1 more Smart Citation